Analytical Solution in the (I-V) Characteristic Curves Calculation of the Corona Plasma Discharge Using the Capacitance Model - Wardaya, Asep Yoyo; Muhlisin, Zaenul; Suseno, Jatmiko Endro; Setiawati, Evi; Hadi, Susilo; Windarta, Jaka (Journal of Physics and Its Applications, 2025)
This research aims to calculate thoroughness among data points and analytical simulation curves in discussing corona discharges' (I-V) characteristics. The electrode construction used is the twin towers with dividing angles to the plane (TTDA-P) model in air, with negative DC polarity. An asymmetrical electrical CCP model in the electrode design uses research variations, including active electrode center clamp angles of q = 300, 450, and 600 and active and passive electrode distances (d) of 0.002 m, 0.005 m, and 0.008 m. The simulation curve comes from the analytical formulation of the reduced capacitance type (inserting a multiplying factor k to the sharp corners of the active electrode), with the simulation program being a Python GUI program. The experimental results produced an appropriate error value (t-test value £0.05) and a high percentage of tangent points value. The best curve was achieved at q = 450 and d = 0.008 m, with a t-test value of 0.0313 and the highest percentage of significant tangent points of 92.31%. For all variations q, there is a tendency that the smaller the value of d (the gap length among two electrodes), the greater the deviation distance between the simulation curve and the data points.